2012
DOI: 10.1111/j.1447-0756.2012.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord presentation after use of a trans‐cervical balloon catheter

Abstract: The use of a TCBC with 180-250 mL of saline increases the risk of cord presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…suggested that the risk of UCP may increase with use of a larger TCBC in Japanese women: the incidences of UCP were 0.0% (0/320) and 0.7% (3/446) among 150‐mL and 200–250‐mL TCBC users, respectively ( P = 0.2693). A recent study confirmed that the incidence of UCP was significantly higher among 180–250‐mL TCBC users than among 70–150‐mL TCBC users (3.3% [2/61] vs 0.0% [0/662], P = 0.00701) . Another study retrospectively examined the incidence of UCP among 15 549 Japanese women with cephalic singleton pregnancies who attempted to give birth vaginally at or after 34 weeks of gestation between 1997 and 2010; the incidence of UCP was one in 753 women (0.13%) who underwent IOL using a 150‐mL TCBC, while the incidence was one in the remaining 14 796 women (0.007%) who did not undergo a TCBC procedure ( P = 0.095).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…suggested that the risk of UCP may increase with use of a larger TCBC in Japanese women: the incidences of UCP were 0.0% (0/320) and 0.7% (3/446) among 150‐mL and 200–250‐mL TCBC users, respectively ( P = 0.2693). A recent study confirmed that the incidence of UCP was significantly higher among 180–250‐mL TCBC users than among 70–150‐mL TCBC users (3.3% [2/61] vs 0.0% [0/662], P = 0.00701) . Another study retrospectively examined the incidence of UCP among 15 549 Japanese women with cephalic singleton pregnancies who attempted to give birth vaginally at or after 34 weeks of gestation between 1997 and 2010; the incidence of UCP was one in 753 women (0.13%) who underwent IOL using a 150‐mL TCBC, while the incidence was one in the remaining 14 796 women (0.007%) who did not undergo a TCBC procedure ( P = 0.095).…”
Section: Discussionmentioning
confidence: 95%
“…Several reports have raised concerns about a possible increased risk of UCP among TCBC users or among women who undergo IOL with unspecified methods . In 1983, Hirashima et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations